Effect of mulching and fertilization on the quality of strawberries - Moor, Ulvi; Karp, Kadri; Põldma, Priit (MTT Agrifood Research Finland, 2004)
A large part of the research carried out with strawberries (Fragaria × ananassa) has been with the aim of gaining higher yields. At the same time postharvest losses are remarkable. Therefore the need for research with the aim of increasing quality is rising. The aim of the present research was to study the influence of mulch (plastic and straw), fertilization and the age of plants (two, three and four years) on the quality of strawberry fruits. Experiments were carried out with cultivar Bounty during 2000 2002 at the Estonian Agricultural University. Results showed that fertilization had a positive effect on the yield of first grade fruits with both mulches. With plastic mulch, fertilization had a positive influence on vitamin C content. With straw mulch, fertilization decreased fruit damage. None of the experimental factors had an impact on the content of soluble solids. We concluded that injecting fertilizer solution into the soil under plastic mulch is an effective and inexpensive way to avoid a decrease in fruit size in the third year of production. Vitamin C content was negatively influenced by plant age, and in the three-year-old plantation, smaller fruits contained more vitamin C than larger fruits.
Keywords: Pu; mansikat; Fragaria ananassa; katteet; lannoitus; Fragaria ananassa; strawberries; mulching; fertilizers; crop quality; vitamin C; fruit cracking; mansikka